Eksplorasi Jamur Alkalotoleran dari Desa Sukolilo Barat, Kecamatan Labang, Kabupaten Bangkalan, Madura, Jawa Timur - Lusiana, Helga; Rukmi, MG Isworo; Raharjo, Budi (Bioma : Berkala Ilmiah Biologi, 2014)
Mold exploration from limestone hills West Sukolilo  village, District Labang, Bangkalan, Madura, East Java,  conducted to found the  alkalotolerant mold isolates and investigate their  amylolytic, proteolytic, and cellulolytic activity. Mold isolation were done using spread plate and dilution method  on  PDA and CMA at pH 8.0, 9.0, and 10.0. Twenty-seven mold isolates have been found consist of  four genus  i.e. Aspergillus, Fusarium, Curvularia, and Trichoderma. The result of amylolytic test  showed Trichoderma longibrachiatum (IMD-26) have the  highest activity at pH 8, while  Fusarium sp 2 (IMD-24) showed the highest activity at pH 9. Aspergillus flavus (IMD-7) showed highest proteolytic activity at pH 8, while Hyphomycete (IMD-27) showed the highest activity at pH 9. The highest cellulolytic activity at pH 8 showed by Trichoderma harzianum (IMD-25) and pH 9 by Fusarium sporotrichoides (IMD-20). Keyword : alkalotoleran mold, amylolytic, proteolytic, cellulolytic.